PENGARUH PERAN KEPEMIMPINAN TERHADAP IMPLEMENTASI TEKNOLOGI BERBASIS APLIKASI DALAM MENINGKATKAN EFEKTIVITAS KERJA PEGAWAI DI PUSKESMAS MENINTING - Syatriawan Perdana Putra (Yayasan Nusantara Hasana Berdikari, 2023)
This research aims to evaluate the influence of leadership roles on the implementation of application-based technology in increasing employee work effectiveness at the Meninting Community Health Center. Puskesmas (Community Health Center) has a vital role in providing community health services at the primary level. This research uses a survey method with a questionnaire as a data collection instrument and simple linear regression data analysis. The research results show that leadership has a significant influence on the implementation of application-based technology. The coefficient of determination shows that around 49.6% of the variability in the implementation of application-based technology at the Meninting Community Health Center can be explained by leadership variables. These results highlight the important role of leadership in influencing employee work effectiveness through the adoption of application-based technology. Therefore, this research provides strong support for the importance of the role of leadership in increasing employee work effectiveness at the Meninting Community Health Center through the implementation of application-based technology.